Validation of the new visual swimming pace control system in real-time - Szczepan, S.; Zaton, K. (Central European Journal of Sport Sciences and Medicine, 2017)
Controlling swimming speed, i.e. the intensity of physical activity, is an important factor in swimming training. The aim of this study was to validate the new "Swimming Pace Control System" (SPCS) for the control of swimming speed in real time using visual information. Submerged at the bottom of the pool was a system equipped with LEDs and software that informed the swimmer of the appropriate distance and swimming speed. A validation test was completed with an accuracy of ±200ms which compared the predetermined time for the beam of light emitted by the SPCS and the times achieved and recorded by the electronic starting system; "Colorado Time System" (Colorado Time, USA). The average time required to move the beam simulated by the SPCS at fixed distances (150 m, 100 m, 50 m) was within the assumed error of measurement (500 ms). SPCS was proven to be useful for control of swimming speed in real-time with the aid of visual information. The system gives an objective indication of swimming speed, thus it can be used in swimming training and during empirical research.